PERSEPSI MASYARAKAT TERHADAP PERUBAHAN LIVELIHOOD ASSETS DI AREA RELOKASI PADA RUMAH SUSUN JATINEGARA BARAT - Rohman, Fatchur; Astuti, Winny; Rahayu, Paramita (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2024)
Settlement Relocation is a program under the Provincial Government of DKI Jakarta that aims to provide decent housing for the community. Kampung Melayu Village is one of the relocation locations implemented in 2015 to the Jatinegara Barat Flat. Settlement relocation has a diverse impact due to differences in community perceptions. So this study aims to determine the community’s perception of changes in livelihood assets in the relocation of settlements along the Ciliwung River in terms of human capital, social capital, physical capital, environmental capital, and financial capital. The method used was scoring analysis and descriptive quantitative through questionnaires and open interviews with the Jatinegara Barat Flats community affected by the relocation. The results of this study show that the people relocated to Jatinegara Barat Flats experienced positive changes toward livelihood assets with an overall score of 70.99%.